2013
DOI: 10.1080/00140139.2013.842656
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of apparent mass responses of human subjects seated on rigid and elastic seats under vertical vibration

Abstract: The apparent mass (AM) responses of human body seated on elastic seat, without and with a vertical back support, are measured using a seat pressure sensing mat under three levels of vertical vibration (0.25, 0.50 and 0.75 m/s(2) rms acceleration) in 0.50-20 Hz frequency range. The responses were also measured with a rigid seat using the pressure mat and a force plate in order to examine the validity of the pressure mat. The pressure mat resulted in considerably lower AM magnitudes compared to the force plate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
4
18
0
Order By: Relevance
“…The limitation of the reported biodynamic models and anthropodynamic manikins may inpart be due to lack of consideration of the human body interactions with an elastic seat that is most representative of the vehicle seating. Owing to the complexities associated with measurements of the driving-point force at the elastic body-seat interface, the vertical AM of the body seated on elastic seats has been attempted only in two reported studies using body-seat interface pressure measurement systems (Hinz et al 2006;Dewangan et al 2013a). These have shown that the AM response of the body seated on an elastic seat is substantially different from that measured with a rigid seat.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The limitation of the reported biodynamic models and anthropodynamic manikins may inpart be due to lack of consideration of the human body interactions with an elastic seat that is most representative of the vehicle seating. Owing to the complexities associated with measurements of the driving-point force at the elastic body-seat interface, the vertical AM of the body seated on elastic seats has been attempted only in two reported studies using body-seat interface pressure measurement systems (Hinz et al 2006;Dewangan et al 2013a). These have shown that the AM response of the body seated on an elastic seat is substantially different from that measured with a rigid seat.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively lower values of the measured AM were attributed to low density of pressure sensors within the sensing mat. Dewangan et al (2013a) measured the AM responses of the body seated on a flat polyurethane foam (PUF) cushion using a resistive pressure sensing mat under vertical vibration controlled at the seat cushion. Substantially lower values of AM magnitudes were observed as in the study by Hinz et al (2006), which was attributed to poor frequency response and resolution of the resistive sensors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study measured the biodynamic response of the seated body exposed to whole-body vibration using resistive pressure sensors for the measurement of the biodynamic force (Dewangan et al, 2013). The study also reported substantially lower magnitudes of apparent mass measured from the resistive pressure sensors compared to a force plate, which was attributed to the limited frequency response of the resistive pressure sensors.…”
Section: Frequency Response Characteristics Of the Flexiforce Sensorsmentioning
confidence: 99%
“…The matrices of such sensors have been widely employed for measurements of grip strength and mapping of static contact pressures on automotive seats, wheelchairs, and hospital beds (Hall, 1997;Ashruf, 2002;Aldien et al, 2005b;Akgunduz et al, 2014). The feasibility of such sensors in a dynamic vibration environment has been explored in a recent study involving measurement of apparent mass response of the seated body to low frequency whole-body vibration (Dewangan et al, 2013). It was suggested that the accuracy of the dynamic measurements would greatly depend upon the bandwidth and frequency response characteristics of the pressure sensing systems.…”
Section: Introductionmentioning
confidence: 99%